Pathways to Cleaner Household Cooking in Lao PDR : An Intervention Strategy - World Bank (Washington, DC, 2013)
The structure of this report reflects the directional organization of the study. Chapter two offers a detailed descriptive analysis of national- and regional-level household fuelwood use, supplemented by a detailed analysis of fuelwood consumption and expenditure among rural and peri-urban households. Chapter three discusses the health and gender-related issues linked to Indoor Air Pollution (IAP) exposure resulting from use of energy-inefficient cook stoves. A detailed analysis of potential exposure and risk factors is given as an example, using data from the case study. Chapter four analyzes household demand for cook stoves and the supply chain in the case study area, while chapter five presents the intervention strategy to promote improved cook stoves. Chapter six proposes a complementary pilot project for promoting the use of household biogas systems utilizing an alternative financing approach. Finally, chapter seven concludes.